ANALISIS PUTUSAN NOMOR 598 PK/PDT/2016 TERHADAP AKTA PERJANJIAN PERKAWINAN YANG TIDAK DICATATKAN DALAM DINAS TERKAIT - Bonggas Prayipto; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2021)
Marriage agreements that are made before a notary public but are not recorded at the related service office, the validity of the agreement is only binding on the parties making it, namely a married couple. This means that the marriage agreement becomes invalid and non-binding for a third party. The decision of the judicial review judge Number 598 PK / PDT / 2016 which states that marital assets obtained during marriage become joint assets that must be divided equally and equally in size is correct. The legal implication of a marriage agreement deed that is not registered with the relevant agency is that it does not reduce the legality of the parties making it. The marriage agreement remains valid for a married couple because of the agreement between the two parties as stipulated in Article 1320 of the Criminal Code regarding the validity of the agreement, namely the agreement. In the Marriage Law, there is no article that regulates or states that a new marriage agreement is valid if it has been registered or legalized, and is not binding for a third party, because the purpose of registration or registration at the related agency is to fulfill the element of publicity so that the third party is aware of the marriage agreement that has been signed. create a husband and wife pair so that in case of a legal incident the third party must comply with the marriage agreement that has been made.